Smith on the practicality and objectivity of moral judgments - Strandberg Caj (Belgrade Philosophical Annual)
The moral problem presented by Michael Smith in his seminal book with the same name consists of three claims that are intuitively plausible when considered separately, but seem incompatible when combined: moral judgments express beliefs about objective moral facts, moral judgments are practical in being motivational, and beliefs are unable to motivate by themselves. An essential aspect of Smith's solution to the moral problem is the contention that moral judgments are both motivating for rational agents and objective. In this paper, I take a close look at Smith's arguments by considering his characterizations of rationality understood as coherence between attitudes. It is suggested that on this understanding of rationality and coherence, it has not been clearly shown that moral judgments are both practical and objective.